Solar ultraviolet-B radiation can affect slug feeding preference for some plant species native to a fen ecosystem in Tierra del Fuego, Argentina - Zaller, Johann G.; Searles, Peter Stoughton; Rousseaux, Maria Cecilia; Flint, Stephan D.; Caldwell, Martyn M.; Sala, Osvaldo Esteban; Ballare, Carlos Luis; Scopel, Ana Leonor
The objectives of this study were to test potential effects of solar ultraviolet-B (UV-B) radiation on (i) foliage nutritional quality and foliage decomposition rates of six plant species of this fen ecosystem (Nothofagus antarctica, Carex curta, C. decidua and C. magellanica; Acaena magellanica and Gunnera magellanica) and (ii) feeding preferences for these plant species of the slug Deroceras reticulatum prevalent in this ecosystem. In a mixed-diet selection slugs were offered leaves of the six species that had been grown for three years in experimental field plots under either near-ambient or reduced solar ultraviolet-B (UV-B) radiation. The chosen characteristics of leaf quality (nitrogen concentration, carbon:nitrogen ratio, specific leaf area) and leaf decomposition rates of the six species varied significantly among species but were not affected by the UV-B treatments. However, there were UV-B treatment effects on slug feeding preference for two plant species. For the tree species, Nothofagus, slugs had consumed only one-third as much foliage grown under near-ambient UV-B radiation as of foliage grown under reduced UV-B by the end of the feeding experiment. In contrast, leaves of the sedge C. decidua that had been grown under near-ambient UV-B were consumed twice as much as leaves grown under reduced UV-B radiation. Consumption of foliage for the other four species was similar for the two UV-B treatments. Additionally, diet selection of the slugs was also significantly affected by prior UV-B conditions under which foliage had been grown. Nothofagus leaves were consumed proportionately less and C. decidua proportionately more if the foliage had been grown under near-ambient UV-B radiation. Fil: Zaller, Johann G. State University of Utah; Estados Unidos Fil: Searles, Peter Stoughton. State University of Utah; Estados Unidos. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Regional de Investigaciones Científicas y Transferencia Tecnológica de La Rioja. - Universidad Nacional de La ...